Metabolically Healthy, but Obese Individuals and Associations with Echocardiographic Parameters and Inflammatory Biomarkers: Results from the CARLA Study - Efremov L (Dove Medical Press, 2020)
Ljupcho Efremov,1 Maria Elena Lacruz,2 Daniel Tiller,3 Daniel Medenwald,1 Karin Halina Greiser,4 Alexander Kluttig,1 Andreas Wienke,1 Sebastian Nuding,5 Rafael Mikolajczyk1 1Institute of Medical Epidemiology, Biostatistics, and Informatics (IMEBI), Interdisciplinary Center for Health Sciences, Medical School of the Martin-Luther-University Halle-Wittenberg, Halle (Saale), Germany; 2Clinical Cancer Register, Saxony-Anhalt, Halle (Saale), Germany; 3IT Department, Data Integration Center, University Hospital Martin-Luther-University Halle-Wittenberg, Halle (Saale), Germany; 4Division of Cancer Epidemiology, German Cancer Research Centre, Heidelberg, Germany; 5Department of Internal Medicine III, University Hospital Martin-Luther-University Halle-Wittenberg, Halle (Saale), GermanyCorrespondence: Rafael MikolajczykInstitute of Medical Epidemiology, Biostatistics, and Informatics (IMEBI), Interdisciplinary Center for Health Sciences, Medical School of the Martin-Luther-University Halle-Wittenberg, Magdeburger Str. 8, Halle (Saale) 06112, GermanyEmail rafael.mikolajczyk@uk-halle.deIntroduction: The research on heterogeneity among obese individuals has identified the metabolically healthy, but obese (MHO) phenotype as a distinct group that does not experience the typical cardiovascular-related diseases (CVD). It is unclear if this group differs with regard to preconditions for CVDs. Our aim was to assess differences in echocardiographic parameters and inflammatory biomarkers between MHO and metabolically healthy, normal weight individuals (MHNW).Methods: The analyses used data from 1412 elderly participants from a German population-based cohort study (CARLA), which collected detailed information on demographic, biochemical, and echocardiographic variables. Participants were subdivided into four groups (MHNW, MHO, MUNW (metabolically unhealthy, normal weight) and MUO (metabolically unhealthy, obese)) based on BMI≥ 30 kg/m2 (obese or normal weight) and presence of components of the metabolic syndrome. The clinical characteristics of the 4 groups were compared with ANOVA or Chi-Square test, in addition to two linear regression models for 16 echocardiographic parameters. The difference in inflammatory biomarkers (hsCRP, IL-6 and sTNF-RI) between the groups was examined with a multinomial logistic regression model.Results: The MHO individuals were on average 64.2± 8.4 years old, with a higher proportion of women (71.6%), low percentage of smokers, larger waist circumference (109.3± 10.5 cm vs 89.1± 10.8 cm, p< 0.0001) and higher odds ratios for hsCRP, IL-6 and sTNF-RI compared to MHNW individuals. Linear regression models revealed greater left atrial (LA) diameter (2.73 (95% CI: 1.35– 4.11) mm), LA volume (7.86 (95% CI: 2.88– 12.83) mL), and left ventricular mass index (LVMI) (11.82 (95% CI: 4.43– 19.22) g/m1.7) in the MHO group compared to the MHNW group.Conclusion: The MHO phenotype is associated with echocardiographic markers of cardiac remodeling (LA diameter, volume and LVMI) and higher odds ratios for inflammatory biomarkers.Keywords: obesity phenotypes, visceral adipose tissue, cardiac remodeling, inflammatory biomarkers